Colecionando músicas com uma câmera: mediações audiovisuais e hipermidiáticas na produção artística das sessions do YouTube - Kumoto, Rafael Togo (2016)
In this work, we aim to analyze a range of imagery, auditory and hypermediatic mediation processes in the video production of the sessions, understood as a circuit of video publications on YouTube website. Inspired by early productions like french blog La Blogothèque’s Take Away Shows and the Black Cab Sessions, designed by British video maker Jono Stevens, the sessions present recordings of improvised, musical acts in places unusual to musical performance, like public monuments, kitchens, classrooms, subways, boats and high traffic areas. Based on the premise that video is far from portraying a faithful reproduction of reality, thus implying processes of translation and representation of events to images and sounds – moreover, implying their circulation on platforms focused on publishing and sharing videos –, our argument takes shape in three stages: first, through the study of visual and auditory perception, basing ourselves on E.H. Gombrich’s inferential theories to comprehend the phenomenon of interpreting light emissions and sound modulations (both constituents of videographic communication) as active processes, based on our expectations, experiences and view of things. Afterwards, we observe the system where the sessions are based on through the exploration of several YouTube features that reinforce its status as a content-aggregator platform; we also present in greater detail some recurring features shared by producers associated with the observed circuit. In a third step, we organize our analysis based on its aspects of expression, content and participation and relevance, by identifying some characteristics considered relevant, such as other media and artistic languages’ traces of visuality, recurring representation themes and participation profiles of the collectives. This way, we can argue that behind the apparent notion of chance, improvisation and informality expressed by the solutions adopted in the sessions’ materialization processes lies a close relationship between the different ways of performing, producing and circulating music communicated in the depicted scenes, and the values and views of things of those who participate in a greater or lesser degree of negotiation inherent to the circuit – including bands and artists, video makers, sound engineers, viewers and sponsoring entities.